Innovations in talent building : Kaivalya Education Foundation - Vohra, Neharika, 1966- (SAGE knowledge. Cases., 2016)
The study documents the practices, successes, failures, and lessons of the team at Kaivalya Education Foundation. It will reflect whether these innovations in building talent can be replicated by other organizations.